1 - Prof. ABDALLA BUJRA, (1938–2025) CODESRIA’s Towering Pillar - Murunga, Godwin R. (CODESRIA Bulletin, 2025)
CODESRIA is ﬁfty-two years old. Although it was formally established in 1973, its ideational origins date back to a conference held in Bellagio, Italy in 1964 on ‘Economic Research in Africa’. Among the ten directors of African-based research institutes invited, only two were African: Professor Adebola Onitiri from the Nigerian Institute of Economic and Social Research at the University of Ibadan (Nigeria), and Professor Omer Osman, then dean of the Faculty of Economics and Social Studies at the University of Khartoum (Sudan). The rest were either French or British. The stark underrepresentation of African directors at the Bellagio conference served as a catalyst for a series of meetings by African scholars in the late 1960s and early 1970s, which came to be abbreviated as CODESRIA (Conference of Directors of Economics and Social Research Institutes in Africa). CODESRIA grew beyond meetings to not only acquire a recognisable name and institutional strength in the 1970s and 1980s but also earn legitimacy among African academics and policy actors. Many of these con- tributed in their own ways to strengthening CODESRIA’s intellectual agenda and cementing the value of its knowledge to shaping policy process across the continent. Throughout its history, CODESRIA has been led by academics who served in policy circles, including Justinian F. Rweyemamu (CODESRIA’s president from 1979 to1981),2 and Samir Amin, and the Council has played a signiﬁcant role in policy debates that have shaped Africa’s history.